The Development of a Learning Laboratory at a Residential Treatment Center for Preadolescent Delinquents - Chernen, Leslie; San Jose State Univ., CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Described is a project conducted to achieve the following three goals: (1) the remediation of reading and arithmetic deficits of preadolescent delinquents; (2) the training of paraprofessional and peer tutors through a system of verbal and written presentation modeling, behavioral rehearsal, and evaluative feedback; and (3) the creation of a continuing learning laboratory based diagnosis, individualized prescription, programmed units, reinforcement and self-charting of progress. The study utilized experimental and control groups. Results indicated considerable gains in achievement by the experimental group in reading and arithmetic as compared to the control group. It is noted that less gain was shown on the reading subtests. (MK)
Sponsoring Agency: National Science Foundation, Washington, DC.
Contract Number: NSF-EPP-75-09299.
ERIC Note: Photographs will not reproduce well; Pages 193-225, Appendix 3, removed due to copyright restrictions.
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement; Delinquency; Educational Diagnosis; Elementary Education; Elementary School Mathematics; Individualized Instruction; Learning Laboratories; Mathematics Instruction; Programed Instruction; Reading; Reading Instruction; Reinforcement; Remedial Mathematics; Remedial Reading; Research; Tutoring; Units of Study; Reports, Descriptive; Reports, Research